Timelike spherical curves according to equiform Bishop frame in 3-dimensional Minkowski space - Elsharkawy, N.; Cesarano, C.; Dmytryshyn, R.I.; Elsharkawy, A. (Carpathian Mathematical Publications, 2023)
In this paper, we study the equiform Bishop formulae for the equiform timelike curves in 3-dimensional Minkowski space where the equiform timelike spherical curves are defined according to the equiform Bishop frame. We establish a necessary and sufficient condition for an equiform timelike curve to be an equiform timelike spherical curve. Furthermore, we give certain characterizations of equiform spherical curves in 3-dimensional Minkowski space, which are timelike with an equiform spacelike principal normal vector.